Analysis Of The Impact Of Service Quality On Public Satisfaction In The Processing Of Certificates Of Impossibility In Bintara Village, West Bekasi, West Java - Rosa Tipany; Ade Irawan (Sean Institute, 2024)
This study aimed to examine the impact of service quality on public satisfaction in obtaining a Certificate of Inability (SKTM) at Bintara Subdistrict, West Bekasi. A quantitative approach was employed, collecting data from 191 respondents who had previously applied for an SKTM. The results revealed that service quality significantly influenced public satisfaction. Specifically, the dimensions of reliability, responsiveness, assurance, and empathy were found to have a positive correlation with satisfaction. However, the study also identified challenges such as low public awareness, the absence of specific regulations regarding sanctions, and a lack of data verification by community leaders. These findings highlight the importance of improving service quality, particularly in terms of reliability, responsiveness, assurance, and empathy, to enhance public satisfaction with SKTM services. The study recommends strengthening the implementation of standard operating procedures, improving data accuracy, and increasing public awareness to address the identified challenges. Ultimately, these recommendations can contribute to a more efficient and effective public service delivery system at the subdistrict level.